2011
DOI: 10.1016/j.pain.2011.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Forebrain medial septum region facilitates nociception in a rat formalin model of inflammatory pain

Abstract: The medial septum is anatomically and functionally linked to the hippocampus, a region implicated in nociception. However, the role of medial septum in nociception remains unclear. To investigate the role of the region in nociception in rats, muscimol, a GABA agonist, or zolpidem, a positive allosteric modulator of GABA(A) receptors, was microinjected into medial septum to attenuate the activity of neurons in the region. Electrophysiological studies in anesthetized rats indicated that muscimol evoked a stronge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 81 publications
2
45
0
Order By: Relevance
“…Also, Kaneko and Hammond indicated that intrathecal injection of bicuculline significantly increased the number of flinches and weighted nociceptive behavior scores in the second phase in rats (Kaneko & Hammond, 1997). Similar to our findings, Lee et al showed that microinjection of muscimol (1 or 2 μg/0.5 μL) into the medial septum of awake rats suppressed both licking and flinching behaviors during the formalin test of inflammatory pain (Lee et al, 2011). Furthermore, intrathecal application of bicuculline, or the glycine receptor antagonist, strychnine, can elicit allodynia (Torsney & Mac-Dermott, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…Also, Kaneko and Hammond indicated that intrathecal injection of bicuculline significantly increased the number of flinches and weighted nociceptive behavior scores in the second phase in rats (Kaneko & Hammond, 1997). Similar to our findings, Lee et al showed that microinjection of muscimol (1 or 2 μg/0.5 μL) into the medial septum of awake rats suppressed both licking and flinching behaviors during the formalin test of inflammatory pain (Lee et al, 2011). Furthermore, intrathecal application of bicuculline, or the glycine receptor antagonist, strychnine, can elicit allodynia (Torsney & Mac-Dermott, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…6b ; t 17 = 2.40, p < 0.05, unpaired t-test). Likewise, intraperitoneal administration of an analgesic dose of morphine 9 (5 mg/kg, n = 7) also abolished F-CPA vs. animals administered with vehicle (n = 7; Fig. 6c ; t 12 = 2.63 p < 0.05, unpaired t-test).…”
Section: Resultsmentioning
confidence: 73%
“…The present study, juxtaposed with our published data, provides evidence which suggests that the medial septum is a nodal centre in the forebrain that modulates a range of behaviours to noxious-aversive stimuli. In this context, we have previously shown that the MSDB facilitates acute nociceptive behaviours and spinal nociceptive transmission in the formalin model of persistent inflammatory pain 9 . In the present study, we report the novel findings that KA-induced lesion of the MSDB region abolished the expression of formalin-induced affective behaviour, which was assessed using the F-CPA task.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations